Knowledge and Awareness Level Regarding Stroke Management in Golden Hours among Medical Students in KSA (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Stroke is a serious medical condition brought on by diminished or interrupted blood flow to the brain.To reduce the cognitive and neurological impairment brought on by stroke, early identification and treatment areessential. Strokes cause death or permanent disabilities globally, with Saudi Arabia’s stroke risk increasing, andby 2030, more people are expected to die from stroke-related causes. Objectives: Our aim was to evaluate theKnowledge and Awareness level of Stroke in general, plus its management during the golden hours among MedicalStudents and interns in Saudi Arabia. Materials and Methods: This was an observational cross-sectional study. Thestudy was conducted in Saudi Arabia from January 2024 to February 2024, targeting medical students and interns.By using the Raosoft calculator, the sample size was estimated, with a confidence level of 95% and a marginalerror of 5%, the minimal sample size was 384. Data were collected through an online questionnaire, entered intoMicrosoft Office Excel Software, and analyzed using IBM Statistical Package for the Social Sciences Statistics forWindows. Results: As regard the knowledge and awareness score about stroke management, there were 58.0% outof 400 participants demonstrated a high level of awareness regarding stroke management within the crucial goldenhours. Moreover, 31.5% of respondents exhibited a moderate level of awareness. However, it is worth noting that10.5% of participants displayed a low level of awareness. Regarding the relation between awareness level of strokemanagement in golden hours and sociodemographic characteristics, there was a statistically significant relation tocollege of medicine (P = 0.0001), present year of study (P = 0.017), present GPA (P = 0.018) and if the participant hadenrolled in neurology training before (P = 0.027). It also shows a statistically insignificant relation to gender and age.Conclusion: The study revealed that there is a relatively high level of awareness regarding stroke management withinthe crucial golden hours, with 58.0% of participants demonstrating a good understanding. This is a positive indicationof knowledge among a significant portion of the surveyed population. However, there is still room for improvement as31.5% showed a moderate level of awareness, and 10.5% displayed a low level of awareness. Comparisons with otherstudies globally and within Saudi Arabia suggest that awareness levels vary, indicating a need for ongoing educationalprograms to enhance knowledge about stroke management and the importance of timely interventions.